2022
DOI: 10.9734/jpri/2022/v34i6a35430
|View full text |Cite
|
Sign up to set email alerts
|

RP HPLC Method Development for Simultaneous Estimation of Etoricoxib and Thiocolchicoside

Abstract: A simple, specific and accurate reverse phase high performance liquid chromatography (RP-HPLC) method was developed and validated for simultaneous estimation of Etoricoxib and Thiocolchicoside in bulk and solid dosage form. Separation was achieved by Zorbax C-18 analytical column having dimension (250mm * 4.6 mm i.d 5.0 µm) using methanol and water (60:40) as mobile phase and flow rate was 0.7ml/min. The detection was carried out at 283 nm wavelength using UV detector. The total chromatographic sample time per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The consistent results observed by many authors, when the Alfvén waves interaction considered [34,67,68]. When the Alfvén waves interact nonlinearly in MHD turbulent plasma, then their spectra steeper the Kolmogorov like spectra (k À5=3 ) studied by Goldreich and Sridhar [41,59,63,64]; Goldstein et al [66]. The strong turbulent studied by Schekochihin et al [69] with slop k À7=3 and observed particle asymptotic behavior in space plasma.…”
Section: Numerical Simulation Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The consistent results observed by many authors, when the Alfvén waves interaction considered [34,67,68]. When the Alfvén waves interact nonlinearly in MHD turbulent plasma, then their spectra steeper the Kolmogorov like spectra (k À5=3 ) studied by Goldreich and Sridhar [41,59,63,64]; Goldstein et al [66]. The strong turbulent studied by Schekochihin et al [69] with slop k À7=3 and observed particle asymptotic behavior in space plasma.…”
Section: Numerical Simulation Resultssupporting
confidence: 72%
“…Figure 2(c-d) shows the formation of localized structures for Alfvén waves at t = 11, 16 and after few step the system reaches to its quasi steady state. The Alfvén waves spread there intensity peaks when the magnetic field intensity raised [63]. shows the global spatial structures, where the perturbation takes energy from the interaction of Alfvén wave and form their complex structures (Figure 2(d)).…”
Section: Numerical Simulation Resultsmentioning
confidence: 99%
“…The standard was prepared by dissolving 1 mg/mL in HPLC grade methanol and filtered through a 0.45 μm nylon filter. The retention time of the standard was compared to the samples (Navneet Kumar et al, 2017;Pushparaj, 2017). The mobile phase used was methanol and water in a ratio of 50:50.…”
Section: Hplc Analysismentioning
confidence: 99%